2005
DOI: 10.1039/b503550c
|View full text |Cite
|
Sign up to set email alerts
|

A surfactant-encapsulated polyoxometalate complex towards a thermotropic liquid crystal

Abstract: A novel surfactant-encapsulated terbium-substituted heteropolyoxotungstate complex [L1]13[Tb(SiW11O39)2].30H2O (SEC-1) bearing mesomorphous groups was successfully prepared by the ionic self-assembling route, exhibiting characteristic thermotropic liquid-crystalline behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 22 publications
1
53
1
Order By: Relevance
“…[13] These materials show it is possible to retain the basic physical and chemical properties of the POM clusters, however, it should be emphasized that mainly electrostatic interactions exist Abstract: Grafting of C-6, C-16 and C-18 alkyl chains onto the hydrophilic Mn-Anderson clusters (compounds 2-4) has been achieved. Exchange of the tetrabutyl ammonium (TBA) with dimethyldioctadecyl ammonium (DMDOA) results in the formation of new polyoxometalate (POM) assemb-A C H T U N G T R E N N U N G lies (compounds 5-6), in which the POM cores are covalently functionalized by hydrophilic alkyl-chains and enclosed by surfactant of DMDOABr.…”
Section: Introductionmentioning
confidence: 99%
“…[13] These materials show it is possible to retain the basic physical and chemical properties of the POM clusters, however, it should be emphasized that mainly electrostatic interactions exist Abstract: Grafting of C-6, C-16 and C-18 alkyl chains onto the hydrophilic Mn-Anderson clusters (compounds 2-4) has been achieved. Exchange of the tetrabutyl ammonium (TBA) with dimethyldioctadecyl ammonium (DMDOA) results in the formation of new polyoxometalate (POM) assemb-A C H T U N G T R E N N U N G lies (compounds 5-6), in which the POM cores are covalently functionalized by hydrophilic alkyl-chains and enclosed by surfactant of DMDOABr.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 showed the polarization microscope images of [PW 11 (c). Wu also obtained thermotropic liquid crystals formed by surfactant-encapsulated polyoxometalate complexes [29,30]. Covalently modified polyoxometalates were reported to form supramolecular gels through hydrogen bonding [31,32].…”
Section: Self-assembly Of Modified Polyoxometalate Complexesmentioning
confidence: 96%
“…With this idea in mind, we used a mesogenic ammonium surfactant carrying azobenzene units (S1) to encapsulate [Tb(SiW 11 O 39 ) 2 ] 13− cluster. [51] Polarized optical microscopy (POM) measurements showed that the resultant (S1) 13 / [Tb(SiW 11 O 39 ) 2 ] complex formed anisotropic fluids upon heating. The high-temperature mesophase of the complex showed flow textures after applying mechani-cal stress, while the low-temperature mesophase was more viscous.…”
Section: Thermal Behavior Of the Surfactant-encapsulated Polyoxometalmentioning
confidence: 99%